2024
DOI: 10.3390/microorganisms12010194
|View full text |Cite
|
Sign up to set email alerts
|

The Networked Interaction between Probiotics and Intestine in Health and Disease: A Promising Success Story

Maria Skoufou,
Christina Tsigalou,
Stergios Vradelis
et al.

Abstract: Probiotics are known to promote human health either precautionary in healthy individuals or therapeutically in patients suffering from certain ailments. Although this knowledge was empirical in past tomes, modern science has already verified it and expanded it to new limits. These microorganisms can be found in nature in various foods such as dairy products or in supplements formulated for clinical or preventive use. The current review examines the different mechanisms of action of the probiotic strains and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 264 publications
0
3
0
Order By: Relevance
“…L. acidophilus will be able to act visceral sensitivity by increasing the opioid and cannabinoid receptors in the intestinal mucosa [ 23–25 ]. However, Hadjimbei et al demonstrated that the lactic ferments S. Thermophilus and Lactobacillus bulgaricus are types of probiotics that enhance the functioning of the intestines, reduce the intensity of infectious diarrhoea, have a positive impact on diarrhoea after antibiotic treatment, and improve the elimination of Helicobacter pylori by 5 to 15% [ 26 , 27 ]. Based on a recent evaluation conducted by So et al .…”
Section: Discussionmentioning
confidence: 99%
“…L. acidophilus will be able to act visceral sensitivity by increasing the opioid and cannabinoid receptors in the intestinal mucosa [ 23–25 ]. However, Hadjimbei et al demonstrated that the lactic ferments S. Thermophilus and Lactobacillus bulgaricus are types of probiotics that enhance the functioning of the intestines, reduce the intensity of infectious diarrhoea, have a positive impact on diarrhoea after antibiotic treatment, and improve the elimination of Helicobacter pylori by 5 to 15% [ 26 , 27 ]. Based on a recent evaluation conducted by So et al .…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics and fermented soy proteins have already been evaluated in vivo for their ability to improve upper and lower GI tract condition [ 31 , 32 ]. Indeed, there is highly supportive evidence that probiotic improve overall GI symptoms [ 19 , 33 ] and abdominal pain in irritable bowel syndrome (IBS) [ 34 ], and reduce the risk of antibiotic-associated diarrhoea [ 35 ] and side effects associated with Helicobacter pylori eradication therapy [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms in spontaneously fermented foods have been empirically used for these purposes (Leeuwendaal et al, 2022 ). Subsequent studies have revealed that only certain live microbial strains in abundant quantities can confer health benefits to the host, mainly by enhancing metabolic functions, strengthening the mucosal intestinal barrier, protecting against pathogens, and stimulating the immune system (Campaniello et al, 2023 ; Skoufou et al, 2024 ). Scientific advances in the field have promoted the expansion and diversification of products containing live bacteria, including probiotic food supplements commonly used to ameliorate intestinal and general health, live biotherapeutic products intended to prevent or treat several diseases, and fecal microbiota that, once transferred from healthy donors to individuals with intestinal disorders, can restore the gut microbial balance (Mcilroy et al, 2019 ; Cordaillat-Simmons et al, 2022 ; Franciosa et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%